2004
DOI: 10.1111/j.1365-2141.2004.04998.x
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin system expression in rat bone marrow haematopoietic and stromal cells

Abstract: SummaryThe existence of a bone marrow renin-angiotensin system (RAS) is evidenced by the association of renin, angiotensin converting enzyme (ACE), and angiotensin (Ang) II and its AT 1 and AT 2 receptors with both normal and disturbed haematopoiesis. The expression of RAS components by rat unfractionated bone marrow cells (BMC), haematopoietic-lineage BMC and cultured marrow stromal cells (MSC) was investigated to determine which specific cell types may contribute to a local bone marrow RAS. The mRNAs for ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 40 publications
(42 reference statements)
9
90
0
1
Order By: Relevance
“…With the objective of identifying a local BM RAS that might function in a hematoregulatory capacity, we previously determined that mRNA and protein for all major components of the RAS were present in BM and that marrow stromal cells have a complete RAS that is capable of generating Ang II. 28 The emerging model of the BM as an ancillary component of atherogenesis is supported by the present study and previous studies in animal models of HC-induced atherosclerosis which exhibited changes in BM consistent with amplified myelopoiesis. Collectively, these data suggest that HC contributes significantly to the functional disruption of BM HSCs.…”
Section: Role Of the Bone Marrow Ras In Production Of Activated Monocsupporting
confidence: 87%
“…With the objective of identifying a local BM RAS that might function in a hematoregulatory capacity, we previously determined that mRNA and protein for all major components of the RAS were present in BM and that marrow stromal cells have a complete RAS that is capable of generating Ang II. 28 The emerging model of the BM as an ancillary component of atherogenesis is supported by the present study and previous studies in animal models of HC-induced atherosclerosis which exhibited changes in BM consistent with amplified myelopoiesis. Collectively, these data suggest that HC contributes significantly to the functional disruption of BM HSCs.…”
Section: Role Of the Bone Marrow Ras In Production Of Activated Monocsupporting
confidence: 87%
“…Considering that the BM is a highly organized and complex organ system that gives rise to all mature and circulating blood cells, and that BM has been shown to carry a complete RAS (Strawn et al, 2004), it is reasonable to suggest that local Ang II can be responsible for ROS production in the BM of 2K1C hypertensive mice. However, given the ubiquitous nature of the RAS, separating the effects of circulating and localized Ang II is quite difficult.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Within the marrow microenvironment, HSC and committed haematopoietic precursors interact with the local MSC, which are crucial to normal bone marrow function in that they provide the majority of necessary growth factors for the regulation of haematopoietic cell development. 18,19 Since human HS-5 MSC express AT 1 -receptor mRNA 15 and we showed that rat MSC express AT 1 -and AT 2 -receptor mRNA and protein, 17 regulation of MSC function may represent an additional pathway by which Ang II influences haematopoiesis. Arachidonic acid (AA), a biologically active fatty acid released by MSC, modulates differentiation of HSC and erythroid and myeloid precursors through eicosanoid metabolites and the production of haematopoietic regulatory factors, 20,21 and may also directly alter the function of HSC.…”
Section: Introductionmentioning
confidence: 99%
“…Protein for AT 1 -and AT 2 -receptors was analysed by flow cytometry using a 1:100 dilution of rabbit polyclonal antibodies determined by the manufacturer to cross-react with rat and human AT 1 -and AT 2 -receptors (Research Diagnostics, Inc., Flanders, NJ, USA) and which we previously showed detect AT 1 -and AT 2 -receptors in rat MSC. 17 A secondary FITCconjugated anti-rabbit IgG antibody (1:200 dilution) was used as a fluorescent tag; analysis of secondary antibody alone was included as a negative control.…”
Section: Marrow Stromal Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation